First Report of Groundnut Ringspot Virus Infecting Mungbean in Argentina - Varela, Gonzalo Matías; Lopez Lambertini, Paola Maria; Rodriguez Pardina, Patricia (Wiley, 2025)
Mungbean (Vigna radiata) is a plant species native to India and widely cultivated worldwide. In recent decades, its production and consumption outside Asia have increased significantly, mainly due to its high protein content. In Argentina, it has been incorporated into production systems to diversify summer crops in the northwest of the country (Vizgarra et al. 2014). Orthotospoviruses cause severe damage to economically important crops in many parts of the world, causing significant losses in yield and product quality (Pappu et al. 2009). In Argentina, groundnut ringspot virus (GRSV, a member of the species Orthotospovirus arachianuli) has been identified as a pathogen affecting several crops. However, there have been no reports of GRSV infecting mungbean, either in Argentina or globally.